Commemoration as symbolic reparation: new narratives or spaces of conflict? - Brown, Kris (Human rights review, 2013)
This article examines the role of commemorative processes as a form of symbolic reparation and their potential use in deeply divided societies. After discussing definitions and contexts of symbolic reparation, it will then explore the tensions inherent in this process as it speedily encounters hybridisation, the construction of narratives of ethnic identity and the political contestation of memory in deeply divided societies. An overarching question will be how symbolic reparation might meaningfully allow for the seeding of human rights norms and values in divided societies, and thus aid the recasting of both inter-communal relations and engagement between citizen and state.